Production of Indole Acetic Acid by Azotobacter sp. - Patil*, Vikram (Recent Research in Science and Technology, 2011)
Six bacterial isolates were isolated from different rhizospheric soils. These isolates were further tested for the production of IAA in a medium with 0, 1, 2 and 5 mg/ml of tryptophan. A low amount of IAA production was recorded by Azotobacter strain without tryptophan addition. Production of IAA in Azotobacter increased with increase in tryptophan concentration from 1 to 5 mg/ml. In presence of 5 mg/ml of tryptophan, Azotobacter produced high levels of IAA. Production of IAA was further confirmed by 3 isolates of Azotobacter (Azb3, Azb5 Azb7) and subsequent TLC analysis. A specific spot from the extracted IAA preparation was found corresponding with the standard spot of IAA with the same Rf value. Azotobacter isolates (Azb3, Azb5 Azb7) showed inhibitory effects on the growth of root elongation at all concentrations of tryptophan compared to control. On the other hand, high concentration of exogenous tryptophan could exhibit toxic effects on plant growth.